Trends Analysis of Non-Hodgkin Lymphoma at the National, Regional, and Global Level, 1990–2019: Results From the Global Burden of Disease Study 2019 - Cai, Wenwen; Zeng, Qingle; Zhang, Xingxing; Ruan, Weiqing (Frontiers in Medicine, 2021)
Background: Non-Hodgkin lymphoma is a common hematologic malignancy. This article aimed to estimate the trends of non-Hodgkin lymphoma (NHL) globally from 1990 to 2019. Methods: Data on the NHL burden were explored from the Global Burden of Disease study 2019. The trends of NHL burden were estimated using age-standardized rate (ASR) and estimated annual percentage change (EAPC). Results: The ASR of NHL incidence showed an increasing trend worldwide from 1990 to 2019, with an EAPC of.56 [95% CI: 0.45–0.66]. Meanwhile, increasing trends were observed in both sexes and in most geographic regions, particularly East Asia (EAPC = 3.57, 95% CI: 3.29–3.86). The most pronounced increasing trends were seen in Georgia (EAPC = 4.7, 95% CI: 4.20–5.21), followed by Belarus and Uzbekistan. However, death and disability-adjusted life years (DALYs) caused by NHL showed decreasing trends globally, in which the respective EAPCs were −0.09 (95% CI: −0.17 to −0.02) and −0.28 (95% CI: −0.35 to −0.22). Decreasing trends were mainly seen in high and high-middle sociodemographic index (SDI) areas. At the national level, the largest increasing trends of death and DALYs were observed in Georgia, in which the respective EAPCs were 4.54 (95% CI: 4.01–5.07) and 4.97 (95% CI: 4.42–5.52). Conclusions: Decreasing trends of death and DALYs caused by NHL were observed worldwide from 1990 to 2019, but NHL remains a substantial challenge globally. The findings would inform the strategies for reducing the burden of NHL.